Pediatric chronic urticaria: Clinical and laboratory characteristics and factors linked to remission. Issue 3 (14th March 2023) - Sandoval‐Ruballos, Mónica; Domínguez, Olga; Ortiz de Landazuri, Iñaki; Gereda, Daniella; Espinoza Cisneros, Michelle; Quesada Sequeira, Fabriella; Ramos Rodríguez, Sandra Melissa; Machinena, Adrianna; Piquer, Mónica; Folqué, María del Mar; Lozano, Jaime; Jiménez‐Feijoo, Rosa; et al.
Abstract: Background: Chronic urticaria (CU) is defined as the occurrence of wheals/angioedema for ≥6 consecutive weeks. Until now, guidelines and publications addressing CU have focused mainly on adults. As a result, evidence and guidance in the pediatric population are scarce. Methods: This study aims to describe clinical and laboratory findings in pediatric CU and to determine factors associated with remission. Results: 185 patients, 54% female, median age at onset of 8.8 years. Angioedema was present in almost half. The most common type of CU was chronic spontaneous urticaria (CSU) in 74%. At least one atopic comorbidity was found in almost a third (35%). In addition, 8% had an autoimmune disorder (exclusively in CSU) and 9% had a psychiatric condition. Basopenia was found in 67% and was more frequently associated with CSU. The basophil activation test (BAT) was positive in 40%. With regard to remission, being of male sex, angioedema absence, the absence of physical triggers, and eosinophil counts >0.51 × 10 9 /L were associated with shorter CU duration. Conclusion: Atopy is a common condition in pediatric CU. CSU is the most common type. Autoimmune comorbidities and basopenia were significantly more common in CSU. In addition, ours is one of the few studies, assessing BAT utility in the pediatric population, being positive in a relevant percentage (40%). BAT positivity was more frequent in CSU. Our results suggest that the absence of angioedema and physical triggers, male sex, and eosinophil counts >0.51 × 10 9 /L appear to be associated with a better prognosis in terms of remission.